Nepal Mediciti Medical Journal (NMMJ) Declaration Form - Shrestha, Umid (Nepal Mediciti Medical Journal, 2020)
Each author must read the statements on Authorship Responsibility, Criteria and Contributions; Reporting of Conflicts of Interest and Financial Disclosure; and Copyright transfer/Publishing Agreement. Primary/Corresponding Author must sign this Declaration Form. Remaining Author/s should disclose related information via Authorship Statement Form. Instructions for authors are available at https://www.nepjol.info/index.php/nmmj/about/submissions